Alterations of Alternative Splicing Patterns of Ser/Arg-Rich (SR) Genes in Response to Hormones and Stresses Treatments in Different Ecotypes of Rice (Oryza sativa) - Peng ZHANG; Heng DENG; Fang-ming XIAO; Yong-sheng LIU (Journal of Integrative Agriculture, 2013)
Ser/Arg-rich (SR) genes encode proteins that play pivotal roles in both constitutive and alternative splicing of pre-mRNA. However, not much effort has been made to investigate the alternative splicing of their own pre-mRNA. In this study, we conducted comprehensive analyses of pre-mRNA splicing for 22 SR genes in three rice (Oryza sativa L.) ecotypes indica, japonica and javanica. Using different ecotypes we characterized the variations in expression and splicing patterns of rice SR genes in different tissues and at different developmental stages. In addition, we compared the divergence in expression and splicing patterns of SR genes from seedlings of different rice ecotypes in response to hormones application and environmental stresses. Our results revealed the complexity of alternative splicing of SR genes in rice. The splicing varies in different tissues, in different ecotypes, in response to stresses and hormones. Thus, our study suggested that SR genes were subjected to sophisticated alternative splicing although their encoding proteins were involved in the splicing process.